HARIMAU SEBAGAI SUMBER PENCIPTAAN KARYA SENI GRAFIS - Musrianda, Dr. Budiwirman, M.Pd., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2018)
The purpose of the creation of this final task is to visualize a tiger thatloses its habitat and its population is threatened with extinction. This task is made in the form of graphic artwork. The tiger is very important for the forest, because the predatory animal tiger is very important to control the number of other animals that become food.The method of creating artwork, using five stages of preparation stage,elaboration stage, synthesis stage, stage of concept realization and completionstage. Furthermore, there was an exhibition of graphic artwork, serigraphytechnique (stencil print).Through this graphic work, then created ten works of graphic art withstencil print technique with the title (1)Kehilangan Habitat, (2)Terjerat, (3)Ditolong, (4) Dioperasi, (5) Pasca Operasi, (6) Pemangsa Yang Diburu, (7) Mati,(8) Dikuliti, (9) Ditangkap, (10) Kepedulian.Keywords: Population, Tiger, Graphic arts, Serigraphy(stencil print)